A geographical study on Pseudaulacaspis pentagona and its parasitoids in Hungarian highway margins using pheromone traps and molecular markers - Bayoumy, M. H.; Fetyko, K.; Tobias, I.; Konczné Benedicty, Z.; Szita, É.; Kozár, F. (ENTOMOLOGIA HELLENICA, 2011)
A study has been conducted to monitor geographical spread of the white peach scale Pseudaulacaspis pentagona (Targioni Tozzetti) (Hemiptera: Diaspididae) (WPS) and its parasitoid populations in 32 stops of the Hungarian highways (M0. M1, M3, M5 and M7) using pheromone traps during 2009 and 2010. In addition to the data collected in the current study, previous data were used to investigate the population trend of this pest from 2007 to 2010. The number of males recorded in traps placed on highways was much lower than in the sites close to urban areas (M0). Our data support results of previous studies which suggest the spreading of white peach scale by vehicles (“transport vector”). The significant decrease in the WPS male catches from 2007 to 2010 might indicate the lowering of the population levels of this pest in the area of the study. Eight hymenopterous parasitoid species were captured in pheromone traps. Coccophagus sp. was the predominate species in pheromone traps of WPS in M7, how-ever they may be associated with another coccid species. The identity of scale males and some parasitoids was proved by molecular markers.